High‐Speed One‐Photon 3D Nanolithography Using Controlled Initiator Depletion and Inhibitor Transport. Issue 4 (14th December 2021) - Hsu, Shih‐Hsin; Chi, Teng; Kim, Jinwoo; Somers, Paul; Boudouris, Bryan W.; Xu, Xianfan; Pan, Liang
Abstract: Additive manufacturing of sophisticated 3D nanoscale objects commonly uses femtosecond lasers to photopolymerize a light‐sensitive resin using multi‐photon absorption. This nonlinear process provides high accuracy and flexibility in advanced 3D fabrication; however, it typically has limited throughput and high cost. This work makes use of a one‐photon‐based dosage‐nonlinearity to fabricate 3D nanostructures, demonstrating a cost‐effective method for 3D nanolithography using a low‐cost 405 nm continuous‐wave diode laser. This dosage‐nonlinearity is achieved by using controlled depletion of photo‐initiation species in an environment containing inhibiting species. By controlling multiple competing processes, the undesired dose accumulation outside the writing voxel is stopped, and thereby this method creates a confined writing voxel in space. A multiphysics model is developed to numerically study the one‐photon nonlinear photopolymerization process, which is compared with experimental results. Abstract : Multiphoton lithography methods with femtosecond lasers can reliably create sophisticated 3D polymeric nanostructures. By controlling multiple competing processes in free radical polymerization, a one‐photon process is used to achieve a nonlinear response which is verified by a numerical photopolymerization model through the control of inhibition radicals and their diffusion. With this process 3D structures are fabricated using a low‐cost diode laser.